Analysis of Kuro Fish Stock (Eleutheronema tetradactylum, Shaw 1804) Based on Data at the Pekalongan Nusantara Fisheries Port (PPPN in Indonesian) - aliffyana, firanika; Saputra, Suradi Wijaya; Solichin, Anhar (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Kuro fish is a demersal fish that lives in the bottom column of the water. Kuro fish is a catch of gillnet gear with a high economic value. This study aims to determine the size structure, , length-weight relationship, growth parameters, recruitment pattern, mortality rate and exploitation rate of Kuro fish. The research was conducted from June until August 2022 at Nusantara fishing port (PPN) Pekalongan or PPPN. The survey method was used, with data collection of length (mmTL) and weight (gram). Data analysis method using ELEFAN I tool on FiSAT II software. The study's results obtained 216 Kuro fish samples with lengths ranging from 265-690 mmTL. The size of the first time caught () was 441.90 mmTL with a selective fishing gear of 4.35. The length-weight relationship equation of Kuro fish is  with a negative allometric growth pattern. The results of the growth parameter analysis obtained the von Bertalanffy equation , with a value of L∞ of 715.05 mm, K of 1.5 and -0.043 years. Peak recruitment of Kuro fish occurred in August at 16.32%. The total mortality rate (Z) of fish was 2.81/year, the natural mortality rate (M) was 0.97/year, and the fishing mortality rate (F) was 1.84/year. The exploitation rate (E) of fish amounted to 0.66/year, included in the over-exploited category because it has exceeded the optimum (E> 0.5).